2017
DOI: 10.1007/s00468-017-1603-x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in bud burst timing and bud freezing tolerance among interior and coastal seed sources of Douglas fir

Abstract: Key message The Douglas fir provenance Three Valley was found most suitable for planting in mid-Sweden. Greenhouse tests can most likely predict how different Douglas fir provenances will perform in the field. Abstract The need for species that will grow well through ongoing climate change has increased the interest in Douglas fir [Pseudotsuga menziesii (Mirb.) Franco] in Sweden. One of the most common problems seen in plantations of Douglas fir seedlings is damage caused by late spring frost, known to be high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 35 publications
1
13
1
Order By: Relevance
“…Campbell and Sugano ( 1979 ) found that interior Douglas-fir had a lower chilling requirement than coastal Douglas-fir, and observed earlier bud burst in spring for the interior variety. A study performed by Malmqvist et al ( 2017 ) with the same seed origin as in this study, showed the same pattern of earlier bud burst for the interior variety compared to the coastal variety. All interior provenances in this study had started the process of bud development at the time of the freezing temperatures mentioned above and were therefore damaged by frost to a higher extent than the late flushing coastal provenances.…”
Section: Discussionsupporting
confidence: 79%
“…Campbell and Sugano ( 1979 ) found that interior Douglas-fir had a lower chilling requirement than coastal Douglas-fir, and observed earlier bud burst in spring for the interior variety. A study performed by Malmqvist et al ( 2017 ) with the same seed origin as in this study, showed the same pattern of earlier bud burst for the interior variety compared to the coastal variety. All interior provenances in this study had started the process of bud development at the time of the freezing temperatures mentioned above and were therefore damaged by frost to a higher extent than the late flushing coastal provenances.…”
Section: Discussionsupporting
confidence: 79%
“…The cascade and coastal provenances were also found to have superior productivity across a wide range of planting conditions and are expected to be the most productive in climate change across many regions in Europe (Chakraborty et al 2015;Chakraborty et al 2016). Genetic variation in frost damage and resistance have been studied extensively in North America (Emerson et al 2006;St Clair 2006;Bansal et al 2015) but rarely in Europe (but see; Lavadinović et al 2013;Malmqvist et al 2017). Phenology plays an important role in genetic variation in frost tolerance in temperate plants (Cooper et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Phenology plays an important role in genetic variation in frost tolerance in temperate plants (Cooper et al 2019). Interior provenances are likely to have less resistance against late frost in spring because they flush earlier than coastal provenances (St Clair 2006;Wolf 2012;Lavadinović et al 2013;Bansal et al 2015;Malmqvist et al 2017). Coastal provenances, however, may exhibit higher sensitivity to early frost events in autumn because they need longer time for bud set and hardening (Aitken et al 1996;Lavadinović et al 2013;Malmqvist et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations